We burned so bright [compact disc, unabridged] - Klune, TJ (Macmillan Audio, 2026)
The road stretched out before them. No other cars, just the headlights on the blacktop. Above, the cracked moon in a kaleidoscope sky. Husbands Don and Rodney have lived a good long life. Together they've experienced the highest highs of love and family, and lows so low that they felt like the end of the world. Now, the world is ending for real. A rogue black hole is coming for Earth and in a month everything and everyone they've ever known will be gone. Suddenly, after 40 years together, Don and Rodney are out of time. They're in a race against the clock to make it from Maine to Washington State to take care of some unfinished business before it's all over. On the road they meet those who refuse to believe death is coming and those who rush to meet it. But there are also people living their final days as best they know how--impromptu weddings, bright burning bonfires, shared meals, and new friends. And as the black hole draws near, among ball lightning and under a cracked moon in a kaleidoscope sky, Don and Rodney will look back on their lives and ask if their best was good enough. Is it enough to burn bright if nothing comes from the ashes?